Construction of porphyrinic manganese-organic frameworks based on structural regulation for electrochemical determination of nitrobenzene in water and vegetable samples - Wang, Li; Zhang, Mengjie; Li, Yuanyuan; Chen, Xiumei; Qin, Hao; Yang, Jin; Fan, Suhua; Wu, Hai (Frontiers in Chemistry, 2024)
Nitrobenzene (NB) is one of the major organic pollutants that has seriously endangered human health and the environment even in trace amounts. Therefore, it is of great significance to detect trace NB efficiently and sensitively. Herein, a porphyrinic metal-organic framework (MOF) of Mn-PCN-222 (PCN, porous coordination network) was first synthesized by the coordination between Zr6 cluster and tetrakis(4-carboxyphenyl)-porphyrin-Mn(Ⅲ) (MnTCPPCl) ligand. To regulate its structure and the electrochemical properties, a phenyl group was inserted in each branched chain of TCPP to form the TCBPP organic ligand. Then, we used Zr6 clusters and manganese metalloporphyrin (MnTCBPPCl) to synthesize a new porphyrin-based MOF (Mn-CPM-99, CPM, crystalline porous material). Due to the extended chains of TCPP, the rod-shaped structure of Mn-PCN-222 was switched to concave quadrangular bipyramid of Mn-CPM-99. Mn-CPM-99 exhibited higher porosity, larger specific surface area, better electrochemical performances than those of Mn-PCN-222. By using modular assembly technique, Mn-CPM-99 film was sequentially assembled on the surface of indium-tin-oxide (ITO) to prepare an electrochemical sensor (Mn-CPM-99/ITO). The proposed sensor showed excellent electrochemical reduction of NB and displayed three linear response ranges in the wide concentration ranges. The obtained low limit of detection (LOD, 1.3 nM), high sensitivity and selectivity, and good reproducibility of the sensor for NB detection fully illustrate that Mn-CPM-99 is an excellent candidate for electrochemical sensor interface material. Moreover, the sensor was successfully applied to the detection of NB in lake water and vegetable samples showing satisfactory recovery of 98.9-101.8%.